[quotation] 'The process of development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
'The process of development is not primarly concerned with expanding supply of goods and services, but more of enhancing the capabilities of people. There is a need to pay specific attention to the generation and security of entitlements and their...